2005
DOI: 10.1378/chest.127.6.2119
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up Study on Pulmonary Function and Lung Radiographic Changes in Rehabilitating Severe Acute Respiratory Syndrome Patients After Discharge

Abstract: These findings suggest that lung fibrotic changes caused by SARS disease occurred mostly in severely sick patients and may be self-rehabilitated. D(LCO) scores might be more sensitive than HRCT when evaluating lung fibrotic changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
1
11

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(139 citation statements)
references
References 7 publications
6
121
1
11
Order By: Relevance
“…This suggests that the mechanism of lung injury and lung fibrotic changes caused by H1N1 might have a different pathophysiological process compared with other diseases of the lung. H1N1 patients with lung fibrotic changes seem to have the ability for self-rehabilitation, which is similar to SARS cases [33].…”
Section: Discussionmentioning
confidence: 63%
“…This suggests that the mechanism of lung injury and lung fibrotic changes caused by H1N1 might have a different pathophysiological process compared with other diseases of the lung. H1N1 patients with lung fibrotic changes seem to have the ability for self-rehabilitation, which is similar to SARS cases [33].…”
Section: Discussionmentioning
confidence: 63%
“…Sheng et al 22 have shown that viral infection could increase the risk of pulmonary fibrosis. Xie et al 23 found that 45% of patients showed signs of pulmonary fibrosis within 1 month after being infected with SARS‐CoV. Hui 24 revealed that 36% and 30% of patients infected with SARS‐CoV developed pulmonary fibrosis 3 and 6 months after infection.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] As SARS is a disease that has recently emerged, the long-term sequelae are largely unclear. Studies on the lung function outcome of SARS survivors have been reported; [9][10][11][12][13][14][15][16][17][18][19] however, the longest duration of follow up was around 3 years and small numbers of subjects were studied. 18,19 We have previously reported the 6 month 12 and 1 year outcomes 13 from the Prince of Wales Hospital SARS patient cohort, based on the available normative lung function data collected in the 1960s.…”
Section: Introductionmentioning
confidence: 99%